The effect of the light environment on population size of the epiphytic herb, Lepanthes rupestris (Orchidaceae) - Ruiz-Canino, Francheska (2015)
The demographic dynamics of plant populations will depend on the relative role of density-dependent versus density-independent factors on population reg- ulation. Density-independent factors (i.e. changes in climate, fire, hurricanes) will affect plant survival and reproduction within a population in a manner that is independent of the density of individuals.